Analysis the Impact of Covid-19 on Green Accounting and Its Implications on Profitability - Reschiwati Reschiwati; Fran Sayekti; Tasia Veronica (Jurnal Dinamika Akuntansi, 2025)
Purposes: This study investigates the impact of the COVID-19 pandemic on the adoption of green accounting and its consequences for profitability in the consumer goods industry listed on the Indonesia Stock Exchange from 2018 to 2022. Methods: This study utilizes panel data regression analysis conducted with EViews 13 software. The COVID-19 variable is examined both before and during the epidemic. Green accounting measures environmental performance and disclosure, whereas ROA represents profitability. Purposive sampling chose 21 companies that met the given criteria, yielding 86 observations. Findings: The study shows that COVID-19 impacts environmental performance and transparency but has no meaningful impact on profitability. Furthermore, neither environmental performance nor environmental disclosure affects profitability. These results suggest that companies recognize the importance of integrating environmental performance into their operations, including waste management and the efficient use of natural resources, even though these efforts are not directly linked to profitability. This awareness enables companies to anticipate and mitigate the impacts of the pandemic. Furthermore, public ownership, as a control variable, does not significantly influence environmental performance, environmental disclosure, or profitability. Novelty: This study uses COVID-19 variables based on variants according to the research period, namely the Delta variant, the Alpha variant, and the Omicron variant. There has never been a similar study that includes COVID-19 data divided into COVID-19 variants. The next difference is that the Performance and Environmental Disclosure variables function as both Y variables and X variables (intervening). In addition, this study also uses a control variable, namely public ownership.